PENGARUH STRES KERJA, BUDAYA ORGANISASI, KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION GURU SMK RESTUMUNING PEREAN - I Putu Santika; Sili Antari; Yessi Ardianti; Nyoman Purnami (Journal of Applied Management and Accounting Science, 2023)
Turnover intention is the behavior of employees to resign from their jobs in an organization. Turnover intention is a phenomenon that is highly avoided by an organization because a high level of turnover intention can cause an instability in the organization and hamper the achievement of organizational goals. This research aims to examine the partial and simultaneous influences of the variables of work stress, organizational culture, and organizational commitment on the turnover intention of the teachers at the vocational high school (SMK) of Restumuning Perean Tabanan. There are 55 respondents in total. The technique of analysis is multiple linear regression. Based on the partial test results, the work stress has a positive and significant influence toward the turnover intention. The organizational culture has a negative and significant influence toward the turnover intention. The organizational commitment has a negative and significant influence toward the turnover intention. Simultaneously, the work stress, organizational culture and organizational commitment have significant influences toward the turnover intention of the teachers at SMK Restumuning Perean Tabanan.